(untitled) (Journal of Finance, Business and Management Studies, 2024)
The assimilation of Artificial Intelligence (AI) in restaurant industry represents a revolutionary shift. AI has enabled this industry by optimizing the food deliveries to the customers in no time, route optimization by determining the most effective route for each delivery person and for every order as well. AI interacts with the road infrastructure, weather conditions, traffic status and enable the driver to reach his destination in the stipulated time for every order. AI analyses historical data and make predictions for the future by conducting various algorithm based analysis. Artificial Intelligence has also helped the marketers to decide on dynamic pricing structure and keeping their customer alive with them. One of the major task accomplished by AI is usage of Chabot, which has enabled the customers to get personalized solutions of their problems. This paper aims to identify and develop the transformation and revolution, which has been taken place due to the use of AI in shaping consumer behaviour towards online food delivery services by doing an exploratory analysis based on the published literature in Food delivery applications. This paper suggest that AI is not only a medium of getting customer data and promoting sales but also a strong tool to provide customization and develop a future ready ecosystem for restaurant industry. This paper will throw light on the challenges and issues related to Artificial Intelligence (AI) in the restaurant industry.